2020
DOI: 10.1021/acs.jpcc.0c09790
|View full text |Cite
|
Sign up to set email alerts
|

Exciton–Ligand Interactions in PbS Quantum Dots Capped with Metal Chalcogenides

Abstract: Colloidal quantum dots (CQDs) are typically decorated with organic molecules that provide surface passivation and colloidal solubility. An alternate but less studied surface functionalization approach via inorganic complexes can produce stable CQDs with attractive transport and optical properties. Further development of such all-inorganic CQD solids is dependent on the deeper understanding of the energetic and dynamic interactions of the new ligands with the CQD excitons. Herein, a series of four metal chalcog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Thea uthors suggest that the excitons can be trapped by the inter-dot ligands,which quench the photoluminescence from the corelevel excitons. [62] Additionally,R ossi et al reported that Fçrster resonance energy transfer occurs between CsPbBr 3 nanocrystals and ligands based on perylene diimide,w hich causes emission from the ligands. [63] Based on previous studies of traditional quantum dot systems,s uch as PbS and CdS, [64] we expected to have ligand-exciton interactions or trapping phenomena.…”
Section: Methodsmentioning
confidence: 99%
“…Thea uthors suggest that the excitons can be trapped by the inter-dot ligands,which quench the photoluminescence from the corelevel excitons. [62] Additionally,R ossi et al reported that Fçrster resonance energy transfer occurs between CsPbBr 3 nanocrystals and ligands based on perylene diimide,w hich causes emission from the ligands. [63] Based on previous studies of traditional quantum dot systems,s uch as PbS and CdS, [64] we expected to have ligand-exciton interactions or trapping phenomena.…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggest that the excitons can be trapped by the inter‐dot ligands, which quench the photoluminescence from the core‐level excitons. [62] Additionally, Rossi et al. reported that Förster resonance energy transfer occurs between CsPbBr 3 nanocrystals and ligands based on perylene diimide, which causes emission from the ligands.…”
Section: Improving the Performance Of Leds Through Defect Passivationmentioning
confidence: 99%
“…K 4 GeS 4 ). The authors suggest that the excitons can be trapped by the inter‐dot ligands, which quench the photoluminescence from the core‐level excitons [62] . Additionally, Rossi et al.…”
Section: Improving the Performance Of Leds Through Defect Passivationmentioning
confidence: 99%
“…[23][24][25][26] In the study of Brown et al, ultraviolet photoelectron spectroscopy and density functional theory calculations were used to show that the ligands can significantly influence the position of the Fermi level in relation to valence and conduction bands. 27 Moreover, the ligand choice also influences the stability of the solid film as well as the formation of trap states, as shown in the time-resolved photoluminescence study of Papagiorgis et al 28 Even small surface modifications can drastically enhance the efficiency of absorption as shown in the study of Giansante et al where they were able to enhance the absorption by 300%. 29 Eventually, the search for most optimal ligands moved the research towards inorganic halide ligands.…”
Section: Introductionmentioning
confidence: 99%